Исследование фотоэлектрических свойств симметричной гетероструктуры "окисел–InSe–окисел" - Kovalyuk, Z. D.; Katerynchuk, V. M.; Sydor, O. N. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The possibility of fabricating an n–p–n type phototransistor based on a double heterostructure “oxide–InSe–oxide” is demonstrated. Photocurrent amplification in the phototransistor occurs only for initial sample thicknesses comparable to the diffusion length of minority charge carriers. A distinctive feature of the amplification is the transition of the phototransistor from a high-resistance to a low-resistance state at certain voltages and illumination levels. The higher the illumination level, the lower the transition voltage. The current density through the phototransistor during such a transition can reach 60–100 mA/cm².